Parametric Study of Factors Affecting Lateral Stability of a Public Transportation Vehicle (http://dx.doi.org/10.31427/IJSTT.2021.4.2.5, 2021)
The availability of public transport is one of the solutions to traffic congestion in Jakarta. Focusing on angkot, one of the public transport types in Jakarta, this study discusses a model and simulations to investigate several factors that affect its lateral stability. Those factors include rear tire inflation pressure, passenger configuration, velocity, and downhill inclination angle. The results show that the stability of an angkot is proportional to the rear tires cornering stiffness. It also has an indirect relationship with the passenger configuration within the angkot. Moreover, the stability of an angkot decreases as its velocity and the angle of the inclined road increase. In general, this study is expected to have a contribution to the development of public transport in Jakarta, especially angkot.